Lost in the moment and found - McGuire, Seanan (McGuire, Seanan. Wayward children, 2023)
"A young girl discovers an infinite variety of worlds in this standalone tale in the Hugo and Nebula Award-wining Wayward Children series from Seanan McGuire, Lost in the Moment and Found. Welcome to the Shop Where the Lost Things Go. If you ever lost a sock, you'll find it here. If you ever wondered about favorite toy from childhood... it's probably sitting on a shelf in the back. And the headphones that you swore that this time you'd keep safe? You guessed it.... Antoinette has lost her father. Metaphorically. He's not in the shop, and she'll never see him again. But when Antsy finds herself lost (literally, this time), she finds that however many doors open for her, leaving the Shop for good might not be as simple as it sounds. And stepping through those doors exacts a price. Lost in the Moment and Found tells us that childhood and innocence, once lost, can never be found"--